Fostering Student Creativity in Islamic Religious Education: Strategies of Elementary School Teachers in Central Java - Sangadah, Siti; Fatimah, Meti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Data were collected from 2 PAI teachers and 25 Grade V students through classroom observation, semi-structured interviews, and documentation over a two-month period study aims to determine the efforts of Islamic Religious Education teachers in developing student creativity and its impact on learning at Madrasah Ibtidaiyah Gedongan. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study were Islamic Religious Education teachers and fifth-grade students. The results showed that Islamic Religious Education teachers implemented various creative strategies such as the use of varied methods (group discussions, simulations, projects, and question and answer sessions), the use of interesting learning media, and the integration of Islamic values in learning activities. These efforts have an impact on increasing active participation, self-confidence, critical thinking skills, and the ability of students to produce creative works relevant to Islamic Religious Education material. In addition, learning becomes more enjoyable, meaningful, and motivates students to continue to excel. This study concludes that the role of creative, innovative, and planned Islamic Religious Education teachers has a positive influence on the development of creativity and character formation of students. Active and contextual learning strategies can make Islamic Religious Education a subject that not only teaches religious knowledge but also equips students with 21st-century skills, especially creative thinking and problem-solving abilities.